The evolving impact of global, region-specific and country-specific uncertainty - Haroon Mumtazy; Alberto Mussoz (Queen Mary University of London, School of Economics and Finance, 2018)
We develop a dynamic factor model with time-varying parameters and stochastic volatility, estimate it with several variables for a large number of countries and decompose the variance of each variable in terms of contributions from uncertainty common to all countries (global uncertainty), region-specific uncertainty and country-specific uncertainty. Among other findings, the estimates suggest that global uncertainty plays a primary role in explaining the volatility of inflation, interest rates and stock prices, although to a varying extent over time, while all uncertainty components are found to play a non-negligible role for real economic activity, credit and money for most countries.
Keywords: C15; C32; E32; 330; Dynamic Factor Model; Time-Varying Parameters; Stochastic Volatility; Uncertainty Shocks; Global Uncertainty